Pemetaan Persebaran Emisi Pembakaran dan Pengecatan Area Produksi Drum Distributor Aspal - Fanesa Fathimah Zahroh (Prosiding ESEC, 2023)
Aspal production in Indonesia continues to increase in line with road construction developments. One of the asphalt distributor companies in Gresik Regency is a distributor that contributes a significant role in the construction of national and provincial roads. With the increasing distribution of aspal, the emissions from burning and painting the raw materials for asphalt drums also increase so that the emissions produced will also have an impact on the environment around the production area. Under these conditions, the purpose of this research is to find a solution to the resulting emissions which have a significant impact on the environment. This study measures emissions from each production area chimney, which later results from emission measurements will be modeled in the Aermod software to determine the distribution area of emissions resulting from the combustion process and aspal drum painting. From the modeling results, it was found that the concentration of SO2 contributed significantly to the distribution of emissions around the production area. Therefore, with the modeling that has been done, the solution that can be given is the addition of chimneys in the production area, considering that there are still a lot of land areas in the asphalt distributor company and can be used for adding chimneys. With the addition of the chimney, it is expected that the emissions produced can be reduced and the emission distribution area can also be reduced..